Genome-wide characterization of tea plant (Camellia sinensis) Hsf transcription factor family and role of CsHsfA2 in heat tolerance - Zhang, Xuyang (BMC Plant Biol, 2020)
BACKGROUND: Heat stress factors (Hsfs) play vital roles in signal transduction pathways operating in responses to environmental stresses. However, Hsf gene family has not been thoroughly explored in tea plant (Camellia sinensis L.). RESULTS: In this study, we identified 25 CsHsf genes in C. sinensis that were separated by phylogenetic analysis into three sub-families (i.e., A, B, and C). Gene structures, conserved domains and motifs analyses indicated that the CsHsf members in each class were relatively conserved. Various cis-acting elements involved in plant growth regulation, hormone responses, stress responses, and light responses were located in the promoter regions of CsHsfs. Furthermore, degradome sequencing analysis revealed that 7 CsHsfs could be targeted by 9 miRNAs. The expression pattern of each CsHsf gene was significantly different in eight tissues. Many CsHsfs were differentially regulated by drought, salt, and heat stresses, as well as exogenous abscisic acid (ABA) and Ca(2+). In addition, CsHsfA2 was located in the nucleus. Heterologous expression of CsHsfA2 improved thermotolerance in transgenic yeast, suggesting its potential role in the regulation of heat stress response. CONCLUSIONS: A comprehensive genome-wide analysis of Hsf in C. sinensis present the global identification and functional prediction of CsHsfs. Most of them were implicated in a complex gene regulatory network controlling various abiotic stress responses and signal transduction pathways in tea plants. Additionally, heterologous expression of CsHsfA2 increased thermotolerance of transgenic yeast. These findings provide new insights into the functional divergence of CsHsfs and a basis for further research on CsHsfs functions.